Public Perceptions of Ocean-Based Carbon Dioxide Removal: The Nature-Engineering Divide? - Bertram, Christine; Merk, Christine (Frontiers in Climate, 2020)
Public acceptability is a standard element on the list of potential constraints on research and deployment of ocean-based carbon dioxide removal (CDR). We outline past work on the public perceptions and acceptability of ocean-based CDR among laypersons covering the main developments over the past 15 years. We compare and synthesize insights from two distinct strands of literature – one on climate engineering approaches and the other on coastal ecosystem management or blue carbon approaches. We also draw conclusions from studies on land-based CDR for emerging ocean-based approaches. Main determinants of perceptions identified in the past are controllability, environmental impacts, containment, permanence of carbon storage, risks and benefits for the local population as well as to which degree an approach is perceived as natural or engineered. We highlight how these aspects may influence perceptions and acceptability of ocean-based CDR approaches which have not yet been on the agenda of perceptions research. Even though ocean-based CDR approaches cannot be neatly divided into categories, the public's tendency to favor approaches perceived more as natural over approaches perceived more as engineering could result in dilemma between approaches with possibly high carbon sequestration potential but low levels of acceptability and approaches with possibly low sequestration potential but high levels of acceptability. To effectively work towards achieving net-zero carbon emissions by mid-century, however, we need to bridge the gap between natural and engineering-type approaches, also in research, to come up with a broad portfolio of CDR options to complement classic mitigation and adaptation measures.